Population characterization for fruit morphological diversity in Myrica esculenta - Rawale, Gauri; Kumari, Anita (Indian Journal of Agroforestry, 2023)
The current study focused on 11 natural populations of Myrica esculenta Buch-Ham.ex D. Don spread across three districts in Himachal Pradesh. Five trees were chosen from each population. The results revealed a wide range of variation in fruit and seed characteristics. Shogi and Tutu populations were superior to other populations in terms of fruit size. Populations from Shimla region performed better for pulp weight (35.24±0.79a) and Sirmour region performed better for TSS content (20.88±0.39). Natural population variance was higher as compare to mother tree variance for all fruit and seed characters. Population repeatability coefficient was observed higher as compare to mother tree repeatability coefficients. Fruit length was positively correlated with fruit weight and thus they should be considered together in breeding programs. 88% variation was accounted by two principle components in case of fruit and seed traits. Cluster analysis grouped the genotypes into six major clusters and revealed considerable phenotypic diversity in the germplasm. Cluster III showed its significance for TSS, while cluster II showed highest values for fruit size and pulp weight may be especially useful for domestication. In addition, the studied genotypes may be recognized as representative gene pool of natural populations of Myrica esculenta.